Localized accumulation of Xist RNA in X chromosome inactivation - Neil Brockdorff (Open Biology, 2019)
The non-coding RNA Xist regulates the process of X chromosome inactivation, in which one of the two X chromosomes present in cells of early female mammalian embryos is selectively and coordinately shut down. Remarkably Xist RNA functions in cis, affecting only the chromosome from which it is transcribed. This feature is attributable to the unique propensity of Xist RNA to accumulate over the territory of the chromosome on which it is synthesized, contrasting with the majority of RNAs that are rapidly exported out of the cell nucleus. In this review I provide an overview of the progress that has been made towards understanding localized accumulation of Xist RNA, drawing attention to evidence that some other non-coding RNAs probably function in a highly analogous manner. I describe a simple model for localized accumulation of Xist RNA and discuss key unresolved questions that need to be addressed in future studies.